Assessing individual differences in human behavior : new concepts, methods, and findings. (Palo Alto, Calif. : Davies-Black, 1995)
Historical antecedents, current status, and new directions. New methodological concepts. New findings on traditional individual differences variables. New areas of research. Commentaries.
Keywords: Psychology; Individual differences; Individual differences